Correlation between hearing handicap inventory for the elderly screening (HHIE-S) and pure tone audiometry (PTA) test among Malaysian elderly - Camarudin, Noraini; Ahmad, Siti Anom; Minhat, Halimatus Sakdiah; Mohamed, Mohd Hazmi; Raja Adnan, Raja Nurzatul Efah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: The study aims to determine the correlation of the Hearing Handicap Inventory for Elderly Screening (HHIE-S) questionnaire with the pure tone audiometry (PTA) in the Malaysian older adult population. Methods: This cross-sectional study took a random sample of adults ≥60 years in a tertiary hospital. A total of 202 participants completed both the HHIE-S questionnaire and the PTA test. The total HHIE-S score and the PTA result were explored for the correlation using a Kruskal–Wallis and the validity using the receiver operating characteristic curve. Results: A Kruskal–Wallis analysis indicated a significant correlation for the level of hearing impairment (r =.704, p < 0.001) between the HHIE-S score and the PTA result. Comparison between HHIE-S score of 8 and the PTA >25db results gave sensitivity: 87.9%, specificity: 78.4%, positive predictive value: 80.3%, and negative predictive value: 86.6%. Conclusion: This study suggests that the HHIE-S questionnaire is a good and valid screening instrument for hearing impairment detection in the Malaysian older adult population.